Implementasi Aplikasi Document Management System untuk Meningkatkan Efisiensi dan Akurasi Proses Pembiayaan Bank - Riana Sari; Restu Alpiansah (Jurnal Ilmiah Pengabdian dan Inovasi, 2024)
Real Work Lectures (KKN) is one of the programs organized by the Bumigora University campus which involves students in learning activities outside the campus, interacting directly with the community. The aim is to increase students' understanding of practical sharia banking practices and to find out the use of the Document Management System (DMS) application used by Bank NTB Syariah Mataram, especially the Financing Division, as well as to apply the knowledge gained on campus in real life and provide benefits to the company. . The location of the KKN is on Jl. Udayana, Dasan Agung, Mataram. With a focus on the subject of internship activities at Bank NTB Syariah Mataram. With an internship period of 1 month. The methods used in this practice are observation and interviews. Through an observational approach, the author will directly observe the work processes and practices of sharia banking and pay attention in detail to how the document management system (DMS) is applied in financing management. Meanwhile, through interviews, the author gained an in-depth understanding from bank staff and managers regarding internal policies, challenges, and prospects for the Mataram Sharia banking industry. This activity implies that it is hoped that the company will continue to optimize its operational processes using the DMS application and utilize the knowledge and new ideas students bring.